Nonsteroidal sulfamate derivatives as new therapeutic approaches for Neurofibromatosis 2 (NF2) - Yu-chi Shen; Caroline Arellano-Garcia; Rosa E. Menjivar; Ethan M. Jewett; Wolfgang Dohle; Sofiia Karchugina; Jonathan Chernoff; Barry V. L. Potter; Kate F. Barald (BMC, 2019)
Abstract Background Neurofibromatosis 1 and 2, although involving two different tumour suppressor genes (neurofibromin and merlin, respectively), are both cancer predisposition syndromes that disproportionately affect cells of neural crest origin. New therapeutic approaches for both NF1 and NF2 are badly needed. In promising previous work we demonstrated that two non-steroidal analogues of 2-methoxy-oestradiol (2ME2), STX3451(2-(3-bromo-4,5-dimethoxybenzyl)-7-methoxy-6-sulfamoyloxy-1,2,3,4-tetrahydroisoquinoline), and STX2895 (7-Ethyl-6-sulfamoyloxy-2-(3,4,5-trimethoxybenzyl)-1,2,3,4-tetrahydroisoquinoline) reduced tumour cell growth and induced apoptosis in malignant and benign human Neurofibromatosis 1 (NF1) tumour cells. In earlier NF1 mechanism of action studies we found that in addition to their effects on non-classical hormone-sensitive pathways, STX agents acted on the actin- and myosin-cytoskeleton, as well as PI3Kinase and MTOR signaling pathways. Tumour growth in NF2 cells is affected by different inhibitors from those affecting NF1 growth pathways: specifically, NF2 cells are affected by merlin-downstream pathway inhibitors. Because Merlin, the affected tumour suppressor gene in NF2, is also known to be involved in stabilizing membrane-cytoskeletal complexes, as well as in cell proliferation, and apoptosis, we looked for potentially common mechanisms of action in the agents' effects on NF1 and NF2. We set out to determine whether STX agents could therefore also provide a prospective avenue for treatment of NF2. Methods STX3451 and STX2895 were tested in dose-dependent studies for their effects on growth parameters of malignant and benign NF2 human tumour cell lines in vitro. The mechanisms of action of STX3451 and STX2895 were also analysed. Results Although neither of the agents tested affected cell growth or apoptosis in the NF2 tumour cell lines tested through the same mechanisms by which they affect these parameters in NF1 tumour cell lines, both agents disrupted actin- and myosin-based cytoskeletal structures in NF2 cell lines, with subsequent effects on growth and cell death. Conclusions Both STX3451 and STX2895 provide new approaches for inducing cell death and lowering tumour burden in NF2 as well as in NF1, which both have limited treatment options.